Negara Dalam Keadaan Darurat Menurut UUD 1945 - Mirza Sahputra (Jurnal Transformasi Administrasi, 2020)
In the 1945 Constitution of the Republic of Indonesia (1945 Constitution), the provisions concerning emergencies (state of emergency) are regulated in two articles, namely Article 12 which states "the President declares a state of danger. The conditions and consequences of the hazard situation are stipulated by law "and Article 22 Paragraph (1) states," In the case of compulsion concerns, the President has the right to determine government regulations in lieu of laws ". Both point to the same problem, namely conditions that are excluded from normal circumstances. Of course, the understanding of these two articles has different meanings, even though the two articles are equally set against an unusual condition or outside normal circumstances. The purpose of this paper is to provide an overview of the implementation of the state in an emergency according to the 1945 Constitution, the criteria or measures used in determining emergencies in Indonesia. The type of research used is normative legal research, which is research focused on examining the application of the rules or norms in positive law. The results showed the criteria or size in determining an emergency (state of emergency) need to pay attention to the rational basis for the enactment of an emergency that is the existence of reasonable legal needs (reasonable necessity), the existence of danger factors that threaten (dangerous threat), and in time or opportunities that prove to be very limited (limited time). It is recommended that various positive legal instruments should be provided which from the beginning anticipate the possibility of these unusual or abnormal conditions so that the functions of the state organs continue to function as they should